Development and application of a novel color image segmentation technique - Zhang, Weilu (2008)
In this thesis, a graphical user interface (GUI) based color image object segmentation platform, called foreground-background editing tool (FBET), is developed that consists modified dominant color profiled-based segmentation (DCPS) and some further applications. Supervised and unsupervised approach are developed in modified DCPS. On application, FBET provides good performance in foreground-background segmentation, manipulation and composition.